Soil remediation of the San Cristóbal hill dump using microorganisms (Bacillus cereus) in Pampas Tayacaja - Chavarría Marquez, Esmila Yeime (2023)
The objective of this article is to restore soil contaminated by dumps through the microorganism Bacillus cereus. The methodology includes 5 samples of soils contaminated by dumps, where experiments will be carried out, which will be mutually contrasted and it will be determined if the bioremediation microorganism is efficient or not for the restoration of contaminated soil. The results show that a bad practice in solid waste management are illegal dumps that cause soil contamination, this problem afflicts the district of Pampas, specifically in the San Cristóbal hill, in the investigation a sample of the hill was analyzed San Cristóbal where the initial pH, temperature and texture is 7.5 pH, 22 C ° and clayey, respectively, through the remediation method with the Bacillus cereus bacterium, the pH changes and drops to 6.6 pH, the temperature also changes to 21 ° and the texture changes to loamy-sandy, these as final results. Conclusion, it was possible to verify that the Bacillus cereus bacterium shows favorable results for the inhibition of contaminants from solid waste, that is, they are good restorers of contaminated soils, for this reason it was achieved that the pH, temperature and texture change favorably.